2012
DOI: 10.1128/jvi.06843-11
|View full text |Cite
|
Sign up to set email alerts
|

Identical Consensus Sequence and Conserved Genomic Polymorphism of Hepatitis E Virus during Controlled Interspecies Transmission

Abstract: High-throughput sequencing of bile and feces from two pigs experimentally infected with human hepatitis E virus (HEV) of genotype 3f revealed the same full-length consensus sequence as in the human sample. Twenty-nine percent of polymorphic sites found in HEV from the human sample were conserved throughout the infection of the heterologous host. The interspecies transmission of HEV quasispecies is the result of a genomic negative-selection pressure on random mutations which can be deleterious to the viral popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 41 publications
2
32
0
Order By: Relevance
“…Lorenzo et al examined mutations of the HEV genome in primary cell culture (38) and found few (0.3%) genetic changes. Similarly, no nucleotide mutations were found in the full-length consensus sequence amplified after the transmission of the strain from human to swine, which shows adaptation of genotype 3 HEV to both hosts (39). These results suggest that virus adaptation is associated with a limited number of mutations.…”
Section: Discussionmentioning
confidence: 65%
“…Lorenzo et al examined mutations of the HEV genome in primary cell culture (38) and found few (0.3%) genetic changes. Similarly, no nucleotide mutations were found in the full-length consensus sequence amplified after the transmission of the strain from human to swine, which shows adaptation of genotype 3 HEV to both hosts (39). These results suggest that virus adaptation is associated with a limited number of mutations.…”
Section: Discussionmentioning
confidence: 65%
“…This suggests that swine HEV-3 and HEV-4 may not require any adaptation to jump between these two species. A study showing that the consensus sequence of HEV-3 is identical during transmission from human to swine is in agreement with this hypothesis [122]. However, it is still unclear whether strains of HEV-3 and HEV-4 present in other animals can cross the species barrier and infect humans.…”
Section: Inter-species Transmission Of Hevmentioning
confidence: 57%
“…In this case sequence insertions/deletions were not related to any host species determinant. A recent study established the full genomic adaptation of subtype 3f HEV to both human and swine (Bouquet et al, 2012). Subtype 3f HEV might not require any mutations to readily infect both human and swine, but there is as yet no general information on the evolution patterns of zoonotic HEV.…”
Section: Discussionmentioning
confidence: 99%